Using life stories to understand the development of resilience in the underprivileged - Yatela, Zainal Abidin (2019)
Researchers argue that soft skills are more important than hard skills for employability in the 21st century. In Malaysia, most of the graduates who do not secure employment within six months are from underprivileged families; classified as such because of their low income and are commonly referred to as the bottom 40% (B40). The B40 are seen as lacking in soft skills. This qualitative study used life stories as advocated within the narrative inquiry method to examine the protective factors of youths from B40 families. This study is aimed at understanding how they developed resilience and other soft skills, and went on to receive prestigious scholarships and succeed in life. Data were collected from the three participants and six other interviewees using twelve semi-structured interviews. The data were initially analysed manually, after which a computer software was used. Analytical memos and field notes were the other data collection methods. Individual analysis and cross-analysis were done on the three life stories. Although the three participants were different in terms of their gender, home areas, abilities, personalities and socioeconomic status, it was discovered that three main protective factors were similar in their life stories, and they are (a) a warm and supportive environment; (b) discipline and training; and (c) religiosity and spirituality. These protective factors, which according to other studies were unusual in low-income families, were mainly contributed by their authoritative and resilient mothers. It was also found that all three participants: (a) were obedient and compliant; (b) were given responsibilities from young; and (c) experienced different risk factors which were buffered. It is recommended that underprivileged parents are engaged for awareness on, and trained to implement protective factors in their children’s lives from very young; and for underprivileged children to be trained on soft skills even before they start school.